PENGARUH PENGOLAHAN TANAH DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogea L.) - Raharja, Agung; Susilaningsih, Sri Endah Prasetyowati; Pamungkas, Djoko Heru (JURNAL ILMIAH AGROUST, 2018)
This research was aimed to find out the influence of soil treatment and NPK fertilizer dosage on the growth and yield of peanuts (Arachis hypogea L.). Â This research was carried out on the observation area of the Pusat Inovasi Agro Teknologi Â of Gadjah Mada University (PIAT UGM), Kali Tirto Village, Berbah District, Regency Sleman, Special Region of Yogyakarta. The research location is located at an altitude of 115 masl with rainfall of 60 mm / month, the average temperature ranges from 25-35áµ’C, air humidity 50%, soil type of inceptisol. This research was conducted in May - August 2018, this research was arranged Randomized Complete Block Design (RCBD) method consisting of 2 factors, namely the processing of soil and the dose of NPK fertilizer. Observations were analyzed by DMRT at the level of 5%. The first factor is land cultivation consisting of 3 levels, namely without tillage, minimal tillage, maximum tillage. The second factor is the dose of NPK fertilizer using 3 levels, namely the dosage of 100 kg / ha, 150 kg / ha, 200 kg / ha. Each 1 unit combination treatment was repeated 3 times in each plot of land. This research consisted of 9 variables including number of leaves, plant height, flowering age, number of flowers, fresh weight, plant dry weight, yield of plant pods, weight of 100 seeds, and yield per hectare. The results of the analysis showed no interaction except for the flowering age variable with no tillage treatment and 200 kg / ha NPK fertilizer dosage which produced flowers at 20,40 days, while flowering age occurred at the minimum treatment of minimal tillage and 200 kg NPK fertilizer dosage / ha which produces flowers at 24,13 days. Soil treatment has a significant effect on the variable number of flowers. The treatment of NPK fertilizer dosage significantly affected the dry weight variable